K-space trajectory mapping and its application for ultrashort Echo time imaging - Latta, Peter; Starčuk, Zenon; Gruwel, Marco L H; Weber, Michael H; Tomanek, Boguslaw (Magnetic resonance imaging, 2017)
MR images are affected by system delays and gradient field imperfections which induce discrepancies between prescribed and actual k-space trajectories. This could be even more critical for non-Cartesian data acquisitions where even a small deviation from the assumed k-space trajectory results in severe image degradation and artifacts. Knowledge of the actual k-space trajectories is therefore crucial and can be incorporated in the reconstruction of high quality non-Cartesian images. A novel MR method for the calibration of actual gradient waveforms was developed using a combination of phase encoding increments and subsequent detection of the exact time point at which the corresponding trajectory is crossing the k-space origin. The measured sets of points were fitted to a parametrical model to calculate the complete actual acquisition trajectory. Measurements performed on phantoms and volunteers, positioned both in- and off-isocenter of the magnet, clearly demonstrate the improvement in reconstructed ultrashort echo time (UTE) images, when information from calibration of k-space sampling trajectories is employed in the MR image reconstruction procedure. The unique feature of the proposed method is its robustness and simple experimental setup, making it suitable for quick acquisition trajectory calibration procedures e.g. for non-Cartesian radial fast imaging.
Keywords: koleno; Magnetic Resonance Imaging; teoretické modely; fantomy radiodiagnostické; lidé; Calibration; magnetická rezonanční tomografie; Algorithms; kalibrace; hlava; počítačové zpracování obrazu; Artifacts; Knee; Phantoms, Imaging; algoritmy; Head; Models, Theoretical; artefakty; Image Processing, Computer-Assisted; Humans